KONVENSI BERN DAN PERLINDUNGAN HAK CIPTA - Oksidelfa Yanto (Jurnal Surya Kencana Satu : Dinamika Masalah Hukum dan Keadilan, 2016)
The object of copyright protection under the Berne Convention, namely: works of literature and art that encompasses all the results of the fields of literature, science and art in any manner or form any explication. Since the entry into force of the Berne Convention that was classified as Making Law Treaty and open to all countries that are not yet members to immediately become a member by way of ratifying and handed over the instrument of ratification to the Director General of WIPO. The participation of a country as a member of the Convention Barn, give rise to liability in the participating countries to implement national perundang¬undangan in the field of copyright. Especially in terms of law enforcement for the protection of copyrighted works. This relates to the arrangement in the Berne Convention on moral rights ( "droit moral"), author's rights to mengkluim as the creator of a work and the author's right to object to any act that intends to change, reduce or add to the authenticity of the creations that can be harm the honor and reputation of the creator.Keywords: Copyright, ratification, the Berne Convention